Deleveraging, Debt Default Risk, and Enterprise Innovation: Evidence from China - Du, Yu; He, Yifan (Transactions on Economics, Business and Management Research, 2024)
This study, at the micro level, takes the Chinese central government’s implementation of the "deleveraging" policy as a quasi natural experiment. Based on data from listed companies from 2013 to 2017, this study introduces the Metron default distance that balances financial indicators and asset value fluctuations to measure default risk. Therefore, the DID method is used to test the innovation situation of enterprises with high default risk under the "deleveraging" policy. Research has found that companies with significant default risks under policy shocks have significantly improved their innovation levels and increased their innovation achievements. Furthermore, this research studies the mechanism of the "deleveraging" policy on enterprise innovation from three perspectives: enterprise financing, investment, and business management. The implementation of the "deleveraging" policy will enhance the cash holdings and management governance level of enterprises with high default risk, thereby promoting enterprise innovation.